(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
In Ayurveda, Agnimandya (reduced digestive power) is considered as a root cause for all diseases. Agnikumara rasa (B.R Jwaradhikara) is a well-known Ayurvedic formulation used by Ayurvedic practitioners that increases Agni (digestive fire) and is indicated in various diseases with specific Anupana (adjuvant). There are 6 constituents in this formulation and is indicated in the management of vitiation of Kapha and Vata humor. On analysing the properties of the ingredients, it was found that it is predominant of Katu rasa (pungent taste), Thikta rasa (bitter taste), Laghu (light), Ruksha (dry), Tikshna (sharp) properties, Ushna virya (hot potency), Katu vipaka (pungent taste after bio-transformation). These therapeutic properties are responsible for pharmacological actions of the formulation. This review paper is an attempt to analyse the mode of action of this formulation which gives a deep insight about the usage of the formulation with a better understanding, so that the physician can use the formulation according to his logic in conditions other than indicated.